Histopathological evaluation of seven Amazon species of freshwater ornamental armored catfish - Fujimoto, Rodrigo Yudi; Neves, Mikaelle de Souza; Santos, Rudã Fernandes Brandão [UNESP]; da Cruz, Claudinei [UNESP]; Diniz, Daniel Guerreiro; Eiras, Jorge da Costa (Universidade Estadual de Maringa, 2014)
Fish commonly known as acaris or plecos are freshwater armored catfish economically important as a food resource and as ornamental fish. Most of these species are captured in the Amazon region. However, despite its economic importance, there is a lack of knowledge about their biological aspects. Thus, this study aimed to characterize and evaluate the histopathological aspects of important organs as gills, liver, integument and kidney of seven species of armored freshwater ornamental catfish from Guamá River, Pará State, Brazil. All organs showed typical characteristics of organs of other teleosts. In some species, gills and liver showed slight histopathological changes: telangiectasis, edema and morphological changes related to the presence of parasites (Monogenea and Digenea) in the gills, and changes in the arrangement of hepatocytes rows, and vacuolation of hepatocytes in the liver. Thus, the knowledge of the normal structure of organs and changes found can be used as tools for environmental and health monitoring of animals.
Avaliação histopatológica em sete especies de cascudos ornamentais amazônicos
Keywords: Acaris; Environmental quality; Fish; Histology